مدى إمكانية تطبيق معايير التقرير المالي الدولية في بيئة الأعمال السورية - العليص ابراهيم; زحلوط عفراء (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتناول هذا البحث إمكانية تطبيق معايير التقرير المالي الدولية في بيئة الأعمال السورية، وذلك من خلال مدى ملاءمة كل من واقع البيئة الاقتصادية السورية من ناحية النظام الاقتصادي المتبع، ومصدر تمويل المشروعات الاقتصادية السورية، وحجم الأنشطة الاقتصادية، والعلاقات الاقتصادية لسورية مع الخارج، ووجود السوق المالية السورية، وكذلك البيئة القانونية، وتطور نظام تعليم معايير IFRS، وواقع مهنة المحاسبة في سورية، وتبين مدى ملاءمتها لإمكانية التطبيق الفعّال لمعايير IFRS في سورية. خلص البحث إلى نتيجة مفادها بإمكانية تطبيق معايير IFRS في البيئة الاقتصادية والقانونية السورية بعد أن يتم تطويرها إلى مستوى نضوج يتوافق مع تطبيق معايير IFRS ، وكذلك عدم كفاية نظام تعليم معايير IFRS ومهنة المحاسبة في سورية عن تأدية دورهما تجاه تطبيق هذه المعايير. This research deals with the possibility of applying International Financial Reporting Standards in the Syrian business environment, so the researcher analyses reality of the economic environment Syrian (the economic system that is adopted, the source of the financing of Syrian economic projects, the size of economic activities, the economic relations of Syria with the outside, and the presence of the Syrian Securities Exchange), as well as legal environment, the evolution of accounting education of IFRS, and the reality of the accounting profession in Syria, and show their relevance to the possibility of effective application of the IFRS standards in Syria. The researcher concluded that there is possibility of applying IFRS in the Syrian economic and legal environment after it has been developed to the level of maturity consistent with the application of IFRS standards, as well as the inability of the educational system of IFRS and the accounting profession in Syria to perform their role towards the implementation of these standards.